2021
DOI: 10.1016/j.bjid.2021.101600
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 testing disparities across geographical regions from a large metropolitan area in Brazil: Results from a web-based survey among individuals interested in clinical trials for COVID-19 vaccines

Abstract: After more than a year since the novel coronavirus (SARS-CoV-2) disease 2019 or COVID-19 has reached the status of a global pandemic, the number of COVID-19 cases continues to rise in Brazil. As no effective treatment been approved yet, only mass vaccination can stop the spread of SARS-CoV-2 and end the COVID-19 pandemic. Multiple COVID-19 vaccine candidates are under development and some are currently in use. This study aims to describe the characteristics of individuals who have registered in an online platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…These results are particularly useful to develop public strategies and may contribute to designing campaigns to increase PrEP uptake in Brazil. Lastly, our study was conducted before the COVID-19 pandemic, and due to the increased use of digital recruitment for scientific studies [30], a more heterogeneous population would be expected to be reached nowadays.…”
Section: Strengthsmentioning
confidence: 99%
“…These results are particularly useful to develop public strategies and may contribute to designing campaigns to increase PrEP uptake in Brazil. Lastly, our study was conducted before the COVID-19 pandemic, and due to the increased use of digital recruitment for scientific studies [30], a more heterogeneous population would be expected to be reached nowadays.…”
Section: Strengthsmentioning
confidence: 99%
“…They are produced utilising Vero monkey cell lines. The protective effect of a BBIBP-CORV reached 91.25% protection in Brazil and Turkey [ 110 ]. Also, CoronaVac was found to be 65.3% effective against symptomatic COVID-19, 87.5% against hospitalisation, 90.3% against ICU admissions, and 86.3% against deaths [ 111 , 112 ].…”
Section: Sars-cov-2 Vaccine Platformsmentioning
confidence: 99%
“…Indeed, a meta-analytic study showed that the pooled prevalence of healthcare workers testing positive for COVID-19 was between 7 to 11% [ 4 ], compared to 0.46 to 1.82% in a German population-based cohort study [ 5 ]. In a web survey in the Rio de Janeiro metropolitan area, Brazil, in 2020, 42.6% reported ever testing for COVID-19, and the prevalence of a positive PCR results was 16.0%, and of a positive antibody result 10.0%, with no difference across age and comorbidity groups [ 6 ].…”
Section: Introductionmentioning
confidence: 99%